THE ANALYSIS OF STUDENT ANXIETY ON SPEAKING PERFORMANCE AT SMAN 8 MAROS - Mifta Chairianti; Jusmaniar N; Sulviana Sulviana (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
This study aims to describe the types of students' anxiety on speaking performance and the factors that cause students' anxiety on speaking performance. This research was conducted on the eleventh-grade students of SMAN 8 Maros academic year 2023/2024 using a qualitative approach with descriptive qualitative design. The data were collected by questionnaire, and interview. After analyzing the data the researcher found that the types of students' anxiety on speaking performance are Situation-specific Anxiety and Trait Anxiety are the dominant percentages than State Anxiety and the researcher also found the factors caused students' anxiety on speaking performance were Communication Apprehension (students have low intellectual, students also have difficulty with pronunciation and lack of vocabulary), Test Anxiety (students feel anxious during the speaking test because fear of failure, fear of bad grades and affecting the report card), and Fear of Negative Evaluation (students are anxious because they are afraid of being judged, and being laughed at by friends/teacher when they make mistakes).